ARGON RETENTION PROPERTIES OF SILICATE GLASSES AND IMPLICATIONS FOR 40AR/39AR AGE AND NOBLE GAS DIFFUSION STUDIES - Hazelton G.B.; Axen G.; Lovera O. (My University, 2003)
Sized aggregates of glasses (47-84 wt% SiO2) were fused from igneous-derived cohesive fault rock and igneous rock, and step-heated from ~400 to >1,200 °C to obtain their 39Ar diffusion properties (average E=33,400 cal mol-1; Do=4.63×10-3 cm2 s-1). At T<~1,000 °C, glasses containing <~69 wt% SiO2 and abundant network-forming cations (Ca, Fe, Mg) reveal moderate to strong non-linear increases in D and E, reflecting structural modifications as the solid transitions to melt. Extrapolation of these Arrhenius properties down to typical geologic T-t conditions could result in a 1.5 log10 unit underestimation in the diffusion rate of Ar in similar materials. Numerical simulations based upon the diffusion results caution that some common geologic glasses will likely yield 40Ar/39Ar cooling ages rather than formation ages. However, if cooling rates are sufficiently high, ambient temperatures are sufficiently low (e.g., <65-175 °C), and coarse particles (e.g., radius (r)>~1 mm) are analyzed, glasses with compositions similar to ours may preserve their formation ages.